Digital Project-Based Learning and Its Contribution to Students’ Critical Literacy Development under the Independent Curriculum Framework - Anwar Hidayat; Firman Utina; Sabda Ridwan Hanif (Gema Cendekia Institute, 2025)
The rapid expansion of digital technologies and curriculum reform initiatives has intensified the need for instructional approaches that foster students’ critical literacy in meaningful and authentic learning contexts. This study investigates the contribution of Digital Project-Based Learning (DPBL) to students’ critical literacy development within the Independent Curriculum Framework. Employing a mixed-methods research design, the study involved students participating in digitally mediated project-based learning activities that emphasized inquiry, collaboration, and the production of multimodal digital artifacts. Quantitative data were collected through pre-test and post-test measures of critical literacy, while qualitative data were obtained from student reflections and semi-structured interviews to capture learning experiences and perceptions. The quantitative findings reveal a statistically significant improvement in students’ overall critical literacy, with notable gains in analytical reading, evaluative judgment, and responsible engagement with digital texts. Qualitative analysis further indicates that DPBL enhanced student engagement, learner agency, and reflective awareness of information credibility and ethical digital practices. Students reported increased confidence in analyzing diverse information sources, negotiating meaning through collaboration, and communicating ideas critically using digital tools. The integration of digital technologies within project-based learning was found to support deeper cognitive processing and sustained engagement when accompanied by structured guidance and reflective assessment. Overall, the findings suggest that Digital Project-Based Learning is an effective pedagogical approach for strengthening critical literacy in alignment with the goals of the Independent Curriculum Framework. The study contributes empirical evidence to support the implementation of digitally oriented, project-based pedagogies as a means of promoting critical, reflective, and responsible learners in contemporary educational settings.